Perbedaan pengaruh hipnoterapi terhadap tingkat stres atlet pencak silat berdasarkan jenis kelamin - Yulienugroho, Rosyideva; Doewes, Moechsin; Santoso Sabarini, Sri (Universitas Nusantara PGRI Kediri, 2022)
This study aims to 1) find out the effect of hypnotherapy using direct suggestion techniques and regression techniques on reducing stress levels in pencak silat athletes, 2) find out the differences in the effect of hypnotherapy on male and female athletes, and 3) find out whether there is an interaction between hypnotherapy techniques and gender on stress levels in pencak silat athletes. This research is quantitative descriptive research with a quasi-experimental approach. The research design uses a 2x2 factorial. The subjects were 16 athletes (8 males and 8 females) of the Ngawi District martial arts aged 18-21. Perceived Stress Scale (PSS-10) as an instrument to measure stress levels. The data was then analyzed using a two-way ANCOVA test assisted by SPSS version 23. The results showed that 1) There was no difference in the effect of direct suggestion technique hypnotherapy and regression techniques on stress levels in male and female pencak silat athletes (Sig. 0.653>0,05), 2) There is a difference in reducing stress levels between male and female athletes (Sig. 0.005 <0.05), and 3) There is an interaction between hypnotherapy techniques and gender on decreasing stress levels in male and female pencak silat athletes (0.003 <0.05). In conclusion, hypnotherapy effectively reduces stress levels before competing in male and female athletes. The direct suggestion technique has a better effect on reducing stress in male subjects, while the regression technique has a better effect on female subjects.